Біблеїзми в системі епістолярного автопортретування Лесі Українки - Богдан, Світлана; Bohdan, S.K. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті визначено специфіку використання біблеїзмів як одного з найчастотніших інтекстових елементів у будь-якому тексті, зокрема – в листах; встановлено функційно-прагматичні ознаки біблійного інтексту в епістолярних текстах Лесі Українки, що належить до вагомих чинників її мовотворчості та індивідуального стилю; основну увагу зосереджено на аналізі біблеїзмів як засобу особистісного портретування адресантки та різних способах їх семантичних трансформацій. The article is devoted to the paculiarity of a use of biblical expressions as one of frequently used intext elements in any text first of all in letters. It is analysed main ways of its insertion into epistolary text. It is determined functional-pradmatic features of a biblical intertext in an epistolary text of Lesia Ukrainka which belongs to essential fuctors of her works and an individual style. The main attention is concentrated on an analysis of biblical expressions as a method of an own selfportrait of the addresser in different ways of their semantic transformations. It is established functional and stylistic paculiarities of biblical expressions which are the method of determine of an inner world of the addresser and an evaluation of some stereotypes of her behaviour. It is established a correlation between a variation of an explanation of biblical expressions in a dictionary and their functioning in an epistolary speech of Lesia Ukrainka.
Biblical Exspressions in a System of an Epistolary Selfportrait of Lesia Ukrainka
Keywords: біблеїзм; епістолярний текст; портретування; трансформація; a biblical expression; a portrait; a selfportrait; a transformation; Lesia Ukrainka